4-Nonylphenol in Sierra Nevada glaciers, California, USA - Rebecca Lyons; Jonah Lay; Jack Ivey (Arctic, Antarctic, and Alpine Research, 2020)
Persistent organic pollutants are stored in environmental reservoirs globally. Tracking the mass and movement of these pollutants is critical for assessing environmental health for human and wildlife populations. Recently, glaciers have been identified as secondary reservoirs for persistent organic pollutants. Downstream lakes and rivers have increased risk of exposure with climate change and loss of glacier mass. Two glaciers, Palisade and Middle Palisade Glaciers, in the Sierra Nevada Mountains, California, United States, were modeled for total mass of the persistent organic pollutant, 4-nonylphenol (4NP). The model used LiDAR measurements of surface snow and geographic information systems (GIS) to extrapolate vertical and horizontal 4NP gradients. Concentrations of 4NP in surface snow were sampled in locations based on a range of topographical shielding indices and analyzed via gas chromatography–mass spectrometry. The Middle Palisade Glacier, the smaller and more shielded glacier, had a total mass of 1,677 ± 560 kg 4NP/km2. The Palisade Glacier, which is larger and more exposed to atmospheric deposition, held an estimated 3,456 ± 843 kg 4NP/km2. Meltwater concentrations for the Middle Palisade and Palisade Glaciers were 1.3 ± 0.05 μg/L and 6.1 ± 1.3 μg/L, respectively. These values demonstrate that both glaciers store a significant amount of 4NP and will act as secondary sources of 4NP for downstream water bodies.